BEBERAPA FAKTOR YANG MEMPENGARUHI PENCEGAHAN FRAUD DI MASA PANDEMI COVID-19 PADA LEMBAGA PERKREDITAN DESA SE-KOTA DENPASAR - Dewi, Putu Cintya Purnama; Suartana, I Wayan; Astika, Ida Bagus Putra; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to determine the effect of the internal control system, morality, organizational culture and good corporate governance on the prevention of fraud during the Covid-19 pandemic at Village Credit Institutions throughout Denpasar City. The sampling technique in this study is a non-probability sampling technique involving 105 respondents. The data analysis technique in this study uses multiple linear regression analysis. The results show that the internal control system, morality, organizational culture and good corporate governance have a positive and significant effect on preventing fraud during the Covid-19 pandemic at Village Credit Institutions in Denpasar City.